Beyond a Single World: Pedagogy and Relating in Difference - Mikulan, Petra (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2014)
The central notion of my analysis is that the relational values that are privileged by the feminine, if properly addressed in school, could foster a more inclusive and embodied way of addressing the fundamentally masculine origin of knowledge, curriculum planning as well as daily school rituals and cultures. For this reason I evoke the horizon of sense as captured by Irigaray in her two-ness of the world to designate a positive place for feminine subjectivity in the relational economy of the you and I, her and him. The economy of the placenta is evoked as a new form of connectedness enfolding a new kind of communication in a pedagogical interaction - where multiplicities and differences are privileged over sameness. ‘Touch’ is given primacy in the formation of a dialogue that does not appropriate but instead evokes the sharing of a desire in the two-ness of the world.